Synthesis, Cholinesterase Inhibitory Activity And Molecular Docking Study Of Piperidone-Grafted Pyrimidine And Thiazolopyrimidine Derivatives - Basiri, Alireza (2014)
Alzheimer’s disease (AD) is the most common form of dementia among the elderly people. Based on the cholinergic hypothesis, loss of cholinergic neurons in AD patients’ brain leads to the decline of acetylcholine (ACh) neurotransmitter level and eventually causes severe dysfunctions in the cholinergic neurotransmission. Thus, increasing the ACh levels is a promising therapeutic approach to restore the substantial impairment of memory and cognitive dysfunctions in AD patients. The search for new cholinesterase inhibitors is still ongoing worldwide. Inspired by the biological significance of pyrimidine-grafted derivatives, especially in cholinesterase inhibition, seventy-four novel pyrimidine embedded derivatives, namely pyridopyrimidines 6(a-l), pyridopyrimidothiones 7(a-l), N-ethyl-pyridopyrimidothiones 8(a-j), N-ethylmorpholino pyridopyrimidothiones 9(a-j), pyrimidinethiols 11(a-l) and thiazolopyrimidines 13(a-r) were synthesized and evaluated for their cholinesterases inhibitory potential against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE).